Raising river level to improve the condition of a semi‐arid floodplain forest. Issue 2 (4th January 2013) - Souter, Nicholas J.; Wallace, Todd; Walter, Mark; Watts, Richard
ABSTRACT River red gum (Eucalyptus camaldulensis Denhn.) trees along the lower River Murray, Australia, have suffered severe dieback as a result of river regulation and drought. As an environmental flow initiative, the height of the lower River Murray in South Australia was raised during a period of increased flow in the spring and summer of 2005–2006. This was performed by increasing the level of the rivers in channel weirs. This increased the level of anabranch creeks on the Chowilla floodplain and through horizontal recharge freshened the adjacent groundwater, providing water to riparian river red gums. Groundwater depth rose concurrently with the rise in creek level, likely recharging the saline floodplain water table with fresh creek water. Multistate Markov modelling showed that along four creeks, most healthy trees responded positively to the rise in water level and remained healthy 1 year after the surcharge. Healthy trees were three times more likely to respond than stressed trees and thirty times more likely to respond than defoliated trees. Stressed trees were ten times more likely to respond than defoliated trees. Forty eight percent of trees that had no leaves at the start of the study responded to the surcharge by producing new growth. This study demonstrates how existing regulatory infrastructure can be used to manipulate water levels and that the hydrological connection between surface water and groundwater can be used to provide water to riparian trees. Copyright © 2013 John Wiley & Sons, Ltd.